Perkembangan Multimedia Digital dan Pembelajaran - Setyaningsih, Endah (Indonesian Journal of Learning and Instructional Innovation, 2023)
Learning media helps students in constructing knowledge in various world education institutions. Technological developments help learning media become easier to use. Various learning media technologies have also become a trend and even help learning resources across regional boundaries, countries to continents. In the past, multimedia only included sound and text, then along with the development of technology and information, media also experienced rapid development. Until now, multimedia does not only include sound and text, but includes complete text, graphics, animation, images and audio/video. This phenomenon has an extraordinary impact on learning media. So that not a few educators use interesting multimedia learning media so that interest in digital knowledge brings big changes in all things. In particular, educational issues. Digital Multimedia is the use of computers to present and combine text, sound, images, animation, audio and video with tools and links so that users can navigate, interact, create and communicate. Multimedia is often used in the world of informatics. Apart from the world of informatics, multimedia is also adopted by the world of games, and also to create websites.